PERBANDINGAN EFEKTIFITAS JALUR KREDIT DAN JALUR NILAI TUKAR DALAM MEKANISME TRANSMISI KEBIJAKAN MONETER MENGGUNAKAN METODA STRUCTURAL EQUATION MODEL (SEM) PERIODE 1997.1-2004.12 - Nirdukita Ratnawati; Swasti Putri Mahatmi (Muhammadiyah University Press, 2006)
The purpose of this syudy is to compare of effectively of credit and exchange rate channel in transmission mechanism of monetary polcy in Indonesia (1997.1-2004.12). Structural Equation Model method is used for analyzing the data. Credit channel are consist of money supply, deposits total, credit total, investment, GDP and price level. Exchange rate channel are consist of money supply, interest rate of inter banl ell money, exchange rate, net export, GDP and price level.By using SEM method, the result is exchange rate channel more effective than credit channel in transmission mechanism of monetaiy policy in Indonesia. Finally, this study has purpose to Bank of Indonesia as authority to make the priority of exchange rate stability in monetary policy.